2017
DOI: 10.1097/olq.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In-Person Versus Telephone Interviews for Early Syphilis and Human Immunodeficiency Virus Partner Services in King County, Washington (2010–2014)

Abstract: Background The relative effectiveness of in-person versus telephone interviews for HIV/STD partner services (PS) is uncertain. Methods We compared outcomes of in-person versus telephone PS interviews for early syphilis (ES) and newly diagnosed HIV in King County, Washington from 2010-2014. We used multivariable Poisson regression to evaluate indices (number of partners per original patient (OP)) for partners named, notified, tested, diagnosed, and treated (ES only). Analyses controlled for OP age, gender, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Some supervisors felt that without access to current technology, disease intervention specialists may not evolve with the communities they serve and consequently may be unable to connect both literally and figuratively with their patients. Texting or messaging patients and their partners via mobile apps 1,18 21 and telephone interviews 22 may be useful tools for disease intervention specialists to efficiently and effectively locate patients and their sexual partners, particularly patients who are unavailable during traditional business hours, live in remote parts of the state, or report large numbers of online partners. To allow for the integration of telephone and internet technology currently used by patients into disease intervention specialist work, state and local government policies will need to be changed.…”
Section: Technology Complements Disease Intervention Specialist Workmentioning
confidence: 99%
“…Some supervisors felt that without access to current technology, disease intervention specialists may not evolve with the communities they serve and consequently may be unable to connect both literally and figuratively with their patients. Texting or messaging patients and their partners via mobile apps 1,18 21 and telephone interviews 22 may be useful tools for disease intervention specialists to efficiently and effectively locate patients and their sexual partners, particularly patients who are unavailable during traditional business hours, live in remote parts of the state, or report large numbers of online partners. To allow for the integration of telephone and internet technology currently used by patients into disease intervention specialist work, state and local government policies will need to be changed.…”
Section: Technology Complements Disease Intervention Specialist Workmentioning
confidence: 99%
“…Among studies evaluating PS for syphilis published 1975-2003, the median brought-to-treatment index was 0.22 (range 0.05-0.53) 34 . More recent studies from North Carolina and King County, WA have reported indices in this same range (0.15 and 0.26, respectively) 35,36 , though a report from New York City, Philadelphia, Texas and Virginia found that only 9% of cases had at least one infected partner brought to treatment (range 5-14%), suggesting a substantially lower level of success 37 . These metrics give one a sense of what is currently being accomplished through field services without clearly defining the impact of the intervention on syphilis transmission.…”
Section: Elements Of a Renewed Syphilis Control Effortmentioning
confidence: 88%
“…Alternatively, programs can apply a literature-based estimate that each DIS can perform about 400 index patient interviews per year. 22-24 Using the estimate of 400, the change in the number of STD patient interviews per year can be expressed as 400ΔDIS.…”
Section: Methodsmentioning
confidence: 99%